2022
DOI: 10.1093/cercor/bhac407
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality-based sensorimotor adaptation shapes subsequent spontaneous and naturalistic stimulus-driven brain activity

Abstract: Our everyday life summons numerous novel sensorimotor experiences, to which our brain needs to adapt in order to function properly. However, tracking plasticity of naturalistic behavior and associated brain modulations is challenging. Here, we tackled this question implementing a prism adaptation-like training in virtual reality (VRPA) in combination with functional neuroimaging. Three groups of healthy participants (N = 45) underwent VRPA (with a shift either to the left/right side, or with no shift), and per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 101 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…The integration of VR with tools like fNIRS in studies by Wilf et al (2023) showed promising results, demonstrating that VR could effectively modify large-scale cortical connectivity and influence the processing of naturalistic stimuli.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of VR with tools like fNIRS in studies by Wilf et al (2023) showed promising results, demonstrating that VR could effectively modify large-scale cortical connectivity and influence the processing of naturalistic stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias in randomized controlled studies (RCT) was assessed using the revised Cochrane risk of bias (RoB 2) tool ( Sterne et al, 2019 ). All five studies report low risk of bias arising from the randomization process ( Bourgeois et al, 2021 ; Wilf et al, 2021 ; Bourgeois et al, 2022 ; Wähnert and Gerhards, 2022 ; Wilf et al, 2023 ). Only three studies show some concerns about the risk of bias due to deviations from intended intervention ( Bourgeois et al, 2021 ; Wilf et al, 2021 , 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…The sense of embodiment could also be important in the discussion of whether and to what extent sensorimotor adaptation differs between VR and reality. Studies show that visual displacement in VR leads to a similar adaptation (Wilf et al 2021(Wilf et al , 2023Cho et al 2022) and is influenced by similar factors (Gammeri et al 2020) as in prism adaptation. Wähnert and Gerhards (2022), for example, found empirical evidence that the positive relationship between the number of interactions during perturbation and the aftereffect, which is already known from prism experiments (Dewar 1970;Welch 1971;Fernández-Ruiz and Díaz 1999), can be generalised to VR.…”
Section: Sensorimotor Adaptation In Vrmentioning
confidence: 97%
“…All five studies report low risk of bias arising from the randomization process (Bourgeois et al, 2021;Wilf et al, 2021;Bourgeois et al, 2022;Wähnert and Gerhards, 2022;Wilf et al, 2023). Only three studies show some concerns about the risk of bias due to deviations from intended intervention (Bourgeois et al, 2021;Wilf et al, 2021Wilf et al, , 2023. A high risk of bias due to missing outcome data was reported in the study conducted by Wilf et al (2021).…”
Section: Risk Of Biasmentioning
confidence: 95%
“…The risk of bias in randomized controlled studies (RCT) was assessed using the revised Cochrane risk of bias (RoB 2) tool (Figure 3) (Sterne et al, 2019). All five studies report low risk of bias arising from the randomization process (Bourgeois et al, 2021;Wilf et al, 2021;Bourgeois et al, 2022;Wähnert and Gerhards, 2022;Wilf et al, 2023). Only three studies show some concerns about the risk of bias due to deviations from intended intervention (Bourgeois et al, 2021;Wilf et al, 2021Wilf et al, , 2023.…”
Section: Risk Of Biasmentioning
confidence: 99%